Cost and Results of Geological Explorations With the Diamond Drill in the Anthracite Regions of Pennsylvania - Louis A. Riley (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1877)
I DESIRE to submit, for the consideration and information of the members of the Institute, the following data, drawings, and tables, showing what I believe will be interesting information with regard to the diamond drill, and its uses in developing mineral lands. I would first say that the results given have been obtained during the past two years by means of two drilling machines belonging to the Lehigh Valley Coal Company, operating on their coal lands in the Mahanoy, Lehigh, and Wyoming regions. 1st. A tabulated statement, giving location of borings, date, progress, total cost, itemized cost per foot, etc. 2d. Section showing strata bored in Nos. 5 and 10 holes at Mt. Carmel, see Plate VI. 3d. Section showing strata bored in No. 19 hole at Hazleton, see Plate VI. 4th. Photograph and description of drill No. 2. From the first it will be seen that the total number of test-holes bored up to May 1st of this year is 24; 9 of these are in the Mahanoy region, 6 in the Lehigh region, and 10 in the Wyoming region, in all of which cores have been taken for the whole distance. The total distance bored is 9902 feet. The majority of the holes have been put down for the purpose of proving the lower veins of the coal series, and have had to encounter the harder rocks of the coal formation. Much of the distance has been through the lower conglomerates, going in some cases through the coarse egg conglomerate, the foundation of the coal deposit, and to the green sandstone and red shale which underlie it. These lower sandrocks and conglomer¬ates are among the hardest known to geologists, and present a formidable resistance to the exploring drill. This fact must be taken into consideration in comparisons of cost of drilling, and when considered will still further improve the very favorable results I am able to show in my statement of costs. In illustration, I will cite the work of one bit when boring in the upper or softer rocks of the Wyoming region, where 280 feet were obtained without resetting, while in the Lehigh and Mahanoy regions, in the lower and harder rocks, bits set with the same quality of diamonds would only bore from 3 to 20 feet before being worn out. In this connection it may